CHANGES AND CHALLENGES FACED BY READYMADE GARMENT BUSINESS IN THE DIGITAL ERA - Gangalay, Shrishti (PEOPLE: International Journal of Social Sciences, 2019)
Readymade garment industry is also playing a key role in fashion world as well as in countries economy. A tailor made business transform into industry how, when and what kind of strategies required which highlighted in this paper. Change is the natural law, but personalization over globalization in marketing readymade garment business can open a new challenges. Retail services are generally still produced and consumed at the same location (requiring a face-to-face interaction), despite increasing volumes of online sales. Analytical research based upon primary data which collected from manufacturer, wholesalers, retailers, and customer in Pune city through various questionnaires.This paper also made an attempt to highlight, how to convert upcoming challenges into opportunities in readymade garment business. How and what kind of Administrative and Marketing challenges force to change Readymade garment business into an industry in online shopping era.